I'll close my eyes: young children early exposure to structured drawing / Fatin Aliana Mohd Radzi - Mohd Radzi, Fatin Aliana (2021)
As young children engage in visual art activities, they develop an awareness and appreciation of pleasant sensory experiences, which is the beginning of esthetic development. Using art materials such as paint, clay, markers, crayons, cornstarch, and collage materials, children express their individual ideas and feelings. As they view their own creations and those of other children, they learn to value and appreciate differences. The purpose of this paper is to report on a visual art activity that was conducted in a preschool center located in the United States. Various visual arts activities are conducted in the center; however, for the purpose of this paper, the researcher chose to share only one of these activities. The results show that the role of the facilitator is essential, given that cognitive theory suggests that adults need to take an active child-centered approach to assisting the learning process of children.